Osteoinduction Evaluation of Fluorinated Hydroxyapatite and Tantalum Composite Coatings on Magnesium Alloys - Cao, Zheng; Li, Li; Yang, Linjun; Yao, LiLi; Wang, Haiyan; Yu, Xiaoyang; Shen, Xinkun; Yao, Litao; Wu, Gang (Frontiers in Chemistry, 2021)
The magnesium (Mg) alloy has a wide range of biomaterial applications, while the lack of biocompatibility and osteoinduction property impede the osteointegration. In order to enhance the bioactivity of Mg alloy, the composite coating of fluorinated hydroxyapatite (FHA) and tantalum (Ta) was first developed on its surface through thermal synthesis and magnetron sputtering technologies in this study. The samples were characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), energy dispersive spectroscopy (EDS) mapping, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and water contact angle measurement (WCA), which characterized the surface alternation and confirmed the deposition of the target FHA/Ta coating. The results of cell morphology showed that the MC3T3-E1 cells on the surface of Mg/FHA/Ta samples had the largest spreading area and lamellipodia. Moreover, the FHA coating endowed the surface with superior cell viability and osteogenic property, while Ta coating played a more important role in osteogenic differentiation. Therefore, the combination of FHA and Ta coatings could synergistically promote the biological functions, thus, providing a novel strategy for implant design.